Using Interpretative Phenomenological Analysis to Advance Critical Adult Education Research through Social Movement Learning - Will Frankenberger (Adult Education Research Conference, 2024)
This paper aims to explore how the interpretative phenomenological analysis can support the advancement of qualitative research within the field of critical adult education and social movement learning.
Keywords: social movement learning; critical adult education; interpretative phenomenological analysis; qualitative research